THE IMPACT OF ROAD NETWORK LINKAGES FOR REGION SECTORAL GROWTH IN JABODETABEK AREA - Legowo, Poerwaningsih S. (Journal of Indonesian Economy and Business, 2010)
Transportation infrastructures serve as one of the preconditions to improve a regionsâÂ economy. Transportation infrastructure may influence regional economic growth as wellÂ as the regions surrounding it. The objective of the current study is to analyze the influenceÂ of these infrastructures towards economic activity growth (total units, workers, and sectorÂ production) of a region as well as the regions surrounding it. Analysis is also conductedtowards a number of policies of which act as basis for decision making concerningÂ transportation infrastructure development in a region.The area of study consists of Jakarta, Bogor, Depok, Tangerang and Bekasi orÂ commonly referred to as JABODETABEK area. Time series data is used from the period1990- 2006, and encompassing 4 economic activities including trade, transportation,Â home-construction and industry. Together with the data model, estimations are made byÂ using Two Stages Least Squares (2SLS) prediction methods. A simulation model is thenÂ subsequently used with the SIMNLIN procedure.The results of the simulation demonstrate that toll infrastructure investments in eachÂ region generally elevate regional economic growth (PDRB) and its surroundings, exceptÂ for Bekasi. Conversely, road investment policies generally reduce PDRB growth in aÂ region. Moreover, the results of the simulation indicate that the impacts of tolldevelopment increases growth in the home-construction sector in almost all regions.Conversely, policies to increase road investments would reduce growth in the homeconstructionÂ sector in all regions.Keywords: Transportation infrastructure, interregional linkages, economic growth andÂ JABODETABEK area